Pengaruh Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Variabel Interveningnya - Nadya Waluyo; Angela Angela; Osma Setiawan; Chintya Ones Charli (International Forum of Researchers and Lecturers, 2024)
This article discusses a literature review that has an impact on employee performance as the dependent variable, leadership style and work motivation as the independent variable and job satisfaction as the intervening variable. This literature review aims to determine hypotheses that impact each variable so that they can be used for further research. This literature review provides an explanation that: 1) Leadership style has a relationship and influences employee performance. 2) Work motivation has a relationship and influences employee performance. 3) Leadership style has a relationship and influences job satisfaction. 4) Work motivation has a relationship and influences job satisfaction. 5) Job satisfaction has a relationship and influences employee performance. 6) Leadership style has a relationship and influences employee performance through job satisfaction as an intervening variable. 7) Work motivation has a relationship and influences employee performance through job satisfaction as an intervening variable. 8) Leadership style and work motivation have a relationship and influence employee performance through job satisfaction as an intervening variable.